The Effect of Applying the Financial Accounting System on the ‎Bank’s Balance Sheet - Mohamed Tifour, Amina; Kettouche, Achour (Dirassat Journal Economic Issue, 2016)
Banks are one of the most important economic sectors, having a dominant role on the world level. For this, their financial statements were of paramount importance characterizing a source of reliable information in order to make reasonable decisions. However, to cope with current economic developments, Algeria has prepared a new financial accounting system to produce information that represents a sincere and disclosed financial situation.